Lick the star - Coppola, Sofia 1971-; Hayman, Stephanie; Acord, Lance 1964- (The Criterion Collection, 2018)
"A clique of school girls devise a secret plan that they code-name "Lick the Star"." [imdb.com]
Original: USA 1998
Keywords: Film